PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE KUIS TIM TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 23 PADANG - Wiyanti, Arta - (STKIP PGRI Sumbar, 2014)
This research was conducted due to the studentsâ understanding on mathematicsconcepts and their lack of interest in learning. This research was intended toreveal (1) the development of the studentsâ mathematics conceptual understandingby applying team quiz active learning strategy, (2) whether the use of team quizactive learning strategy affected the studentsâ mathematics conceptualunderstanding. This was a pre-experimental research which used one shut casestudy design. The population of the research was the second year student atSMPN 23 Padang who were distributed into 7 classes. Of the population, thestudents in class VIII.2 were chosen as the sample. The data was collected byadministering a quiz and a post-test. The result of the post-test was analyzed bytaking into account the studentsâ average score after the treatment given andcomparing it to the standard score which was 40. Based on the result of dataanalysis, it was figured out that the studentsâ mathematics conceptualunderstanding in the experimental class was 76,58 which was higher than thestandard score. Further, the number of the students who had achieved theMinimum Stadard Score improved from 0% into 68%. Thus, it was concluded thatthe use of team quiz active learning strategy affected the second year studentsâmathematics conceptual understanding at SMPN 23 Padang.